2012
DOI: 10.1007/s11440-012-0184-5
|View full text |Cite
|
Sign up to set email alerts
|

Formation of drying crack patterns in soils: a deterministic approach

Abstract: Soils, as well as most of deformable multiphase porous materials, are likely to suffer from desiccation cracking, leading to the formation of regular crack patterns affecting their permeability. The ensuing crack spacing has often been related to a concept sometimes called ''sequential infilling'': it is assumed that desiccation cracks are formed by successive generations. However, such a concept does not consider the pattern of a simultaneous crack formation at a given moment. Using our desiccation cracking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 28 publications
0
27
0
3
Order By: Relevance
“…First, primary cracks are developed dividing the soil surface into cells, and then subsequent drying tends to subdivide these cells in the form of secondary and tertiary crack families. In addition, the crack patterns observed experimentally by Peron et al showed that the crack network formation can result from the combination of two processes, “sequential infilling” and “simultaneous growing,” since the cracks tend to appear either successively or simultaneously. The sequential infilling occurs to create different families of cracks, but the simultaneous growing can occur within each family.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, primary cracks are developed dividing the soil surface into cells, and then subsequent drying tends to subdivide these cells in the form of secondary and tertiary crack families. In addition, the crack patterns observed experimentally by Peron et al showed that the crack network formation can result from the combination of two processes, “sequential infilling” and “simultaneous growing,” since the cracks tend to appear either successively or simultaneously. The sequential infilling occurs to create different families of cracks, but the simultaneous growing can occur within each family.…”
Section: Discussionmentioning
confidence: 99%
“…The sequential infilling occurs to create different families of cracks, but the simultaneous growing can occur within each family. The “sequential infilling” concept for desiccation cracking should be invoked only when cells of an intact material with a reduced, well‐defined size can be individualized . The initiation of crack is influenced by the two major factors: stress distribution and presence of flaws .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The proposed explanation for the crack patterns shown in Figure 2 relies on the fact that the fracture network has formed during the plastic evolution of a ductile homogeneously deformed material. Other explanations may be related to bonding of an external layer to a rigid substrate (Peron et al, 2013), or to surface instability (Destrade and Merodio, 2011;Boulogne et al, 2015), or to instabilities occurring during shear (Destrade et al, 2008;Ciarletta et al, 2013). initiated with pioneering works by Hill (1962), Nadai (1950), Mandel (1962), Prager (1954), Rice (1977), Thomas (1961), and developed -from theoretical point of view -into two principal directions, namely, the dissection of the specific constitutive features responsible for strain localization in different materials (for instance, as related to the microstructure, Danas and Ponte Castaneda, 2012;Bacigalupo and Gambarotta, 2013;Tvergaard, 2014) and the struggle for the overcoming of difficulties connected with numerical approaches [reviews have been given by Needleman and Tvergaard (1983) and Petryk (1997)].…”
Section: Introductionmentioning
confidence: 99%